Visualization of user interactions with a pressure mapping mobile application for wheelchair users at risk for pressure injuries. Issue 4 (4th July 2022) - Goodwin, Brianna M.; Olney, Christine M.; Ferguson, John E.; Hansen, Andrew H.; Eddy, Byron; Goldish, Gary; Morrow, Melissa M.; Vos-Draper, Tamara L.
ABSTRACT: Pressure injuries for individuals with spinal cord injuries (SCI) are correlated with mortality and are a leading cause for rehospitalizations. The Assisted Weight Shift (AW-Shift©) is a mobile pressure mapping application designed to provide users with a live map view and reminders to perform weight shifts. Novel visualization techniques were used to understand daily distributions of user interaction wit h AW-Shift©. The date and time of system interactions were recorded for six participants with SCI over 7 days (five males/one female, five manual users/one power user, 55.3 ± 17.3 years old, 10.6 ± 6.5 years since injury). Circular frequency plots were created to visualize the time and frequency participants brought the app to the foreground of their phone and received alerts and reminders to complete weight shifts. While some participants used the system regularly throughout the day, others primarily used it before 8am; highlighting the system's importance for regular spot checks and morning wheelchair setup. Participant adherence to weight shift reminders was low suggesting the live pressure map may be more useful. Circular frequency plots can be used by clinicians to more easily review large amounts of patient data. Future work will investigate raw pressure mat data and create a closed-loop weight shift detection algorithm.